PENERAPAN SISTEM DIGITALISASI PADA UMKM DI DESA LUBUK PINANG KABUPATEN MUKO-MUKO, BENGKULU - Pery Praja; Ferry Lismanto Syaiful (Jurnal Hilirisasi IPTEKS, 2021)
In the business world, several factors determine the success of market competitiveness and the business's survival. With the presence of the Covid-19 pandemic, most economic sectors, especially MSMEs, have become stagnant. The number of MSME actors who ultimately have to close their shops or go bankrupt due to their inability to adapt in choosing the right sales and operational strategies during the Covid-19 Pandemic. Therefore, MSME actors must adapt quickly and precisely in dealing with the adverse effects of the Covid-19 Pandemic for MSME actors who are currently pursuing their business. MSME actors should be able to determine the right marketing strategy in balancing changes in consumer consumptive patterns at this time. . Digitizing MSMEs is the latest and most effective way to reduce the possibility of losses suffered by MSME actors. It can be an effective way to stabilize and increase profits for Micro, Small, and Medium Enterprises (MSMEs). The objectives of this activity are 1. to increase the knowledge and understanding of MSME actors in utilizing social media as an effective marketing medium, 2. to increase the knowledge and understanding of MSME actors in utilizing digital bookkeeping applications to increase the effectiveness of business financial activities. This activity has been carried out in Lubuk Pinang Village, Mukomuko Regency. The target of this activity is MSME actors in Lubuk Pinang Village, Mukomuko Regency. The methods used are counseling, training, and monitoring/evaluation. The results obtained from this activity are that MSME actors have sufficient understanding in determining the right marketing strategy during the Covid-19 Pandemic and using assistive smartphone applications in their business operations. From the results obtained, it can be concluded that using the digitalization system in business activities in the MSME sector can reduce losses and increase sales.